The Effect of Interpretation Context In Community Communication - arief, abid fathurrahman; Muta’ali, Abdul (UI Scholars Hub, 2023)
Today’s, general of Muslim community only recognizes one type of recitation method of the Qur'an, specifically riwayat Hafsh 'an Ashim min Tariq Syathibiyah. This recitation became an international standard among qiraat scholars, students, and the general of Muslims. Qiraat sciences collect the principles of different recitation of the Qur'an which are attributed to qiraat scholars (a'immah al-qira'at). Based from Abul Fadhl Ar-Razi's theory about the meaning of Sab'atu Ahruf, the different recitations of the Qur'an (Ikhtilaf al-Qira'ah) have several criteria, including: Differences in nouns (Isim), verbs (Fi'il), cases ( I'rab), adding and subtracting words (Ziyadah wa Naqishah), prioritizing and ending a pronunciation (Taqdim wa Ta'khir), changing letters (Tabdil) and dialect differences (lahjah). This difference of recitations has connection with Arabic morphology (Sharaf), for example in the words